2015
DOI: 10.2337/dc14-2868
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Saxagliptin in Older Participants in the SAVOR-TIMI 53 Trial

Abstract: OBJECTIVETo examine the safety and cardiovascular (CV) effects of saxagliptin in the predefined elderly ( ‡65 years) and very elderly ( ‡75 years) subpopulations of the Saxagliptin Assessment of Vascular Outcomes Recorded in Patients with Diabetes Mellitus-Thrombolysis in Myocardial Infarction 53 (SAVOR-TIMI 53) trial. RESEARCH DESIGN AND METHODSIndividuals ‡40 years (n = 16,492; elderly, n = 8,561; very elderly, n = 2,330) with HbA 1c ‡6.5% (47.5 mmol/mol) and £12.0% (107.7 mmol/mol) were randomized (1:1) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 40 publications
2
60
0
2
Order By: Relevance
“…We identified one primary article and one secondary article for the Examination of Cardiovascular Outcomes with Alogliptin versus Standard of Care (EXAMINE) trial [28, 45], one primary article and two secondary articles for the Saxagliptin Assessment of Vascular Outcomes Recorded in Patients with Diabetes Mellitus (SAVOR)–Thrombolysis in Myocardial Infarction (TIMI) 53 (SAVOR-TIMI 53) trial [43, 46, 47], and one primary article for the Trial to Evaluate Cardiovascular Outcomes after Treatment with Sitagliptin (TECOS) [44]. Overall, EXAMINE, SAVOR-TIMI 53, and TECOS found no evidence that DPP-4 inhibitor therapy alters MACE risk relative to placebo [28, 43, 44, 48].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified one primary article and one secondary article for the Examination of Cardiovascular Outcomes with Alogliptin versus Standard of Care (EXAMINE) trial [28, 45], one primary article and two secondary articles for the Saxagliptin Assessment of Vascular Outcomes Recorded in Patients with Diabetes Mellitus (SAVOR)–Thrombolysis in Myocardial Infarction (TIMI) 53 (SAVOR-TIMI 53) trial [43, 46, 47], and one primary article for the Trial to Evaluate Cardiovascular Outcomes after Treatment with Sitagliptin (TECOS) [44]. Overall, EXAMINE, SAVOR-TIMI 53, and TECOS found no evidence that DPP-4 inhibitor therapy alters MACE risk relative to placebo [28, 43, 44, 48].…”
Section: Resultsmentioning
confidence: 99%
“…Multivariable analyses revealed that subjects at greatest risk of hospitalization for HF had previous HF (adjusted HR 4.18; 95% CI 3.48–5.02), an eGFR ≤60 mL/min (adjusted HR 2.00; 95% CI 1.65–2.42), or elevated baseline levels (quartile 4) of N-terminal pro B-type natriuretic peptide (adjusted HR 5.51; 95% CI 4.24–7.16) [46]. Risk of MACE in SAVOR-TIMI 53 was similar among elderly (≥65 years, HR 0.92; 95% CI 0.79–1.06; <65 years, HR 1.15; 95% CI 0.96–1.37; interaction P value 0.06) and very elderly (≥75 years, HR 0.95; 95% CI 0.75–1.22; <75 years, HR 1.01; 95% CI 0.89–1.15; interaction P value 0.67) patients who received saxagliptin and placebo [47]. The increased risk of HF-associated hospitalization with saxagliptin relative to placebo was similar regardless of age group [47].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent retrospective subgroup analysis (279 patients, 65 years of age and older) evaluating saxagliptin 5 mg daily vs. placebo demonstrated the clinically relevant and significant efficacy of saxagliptin in reducing A1C levels in older patients (37). The recently published Saxagliptin Assessment of Vascular Outcomes Recorded in Patients with Diabetes Mellitus (SAVOUR-TIMI) trial also supports the use of DDP-4 inhibitors in the elderly because they are simple, once-daily agents that incur no risk for hypoglycemia (38). However, their use is limited in most countries due to high cost.…”
Section: Use Of Glucose-lowering Medicationsmentioning
confidence: 91%
“…Few studies specifically in older adults with type 2 diabetes exist, limiting the applicability of the evidence to older, complex patients (11)(12)(13)(14)(15)(16). In recognition of the particular pathophysiologic features of older patients with diabetes, the International Diabetes Federation (IDF) and the American Diabetes Association (ADA) developed guidelines specifically for the older population.…”
mentioning
confidence: 99%